Progress in particle-based multiscale and hybrid methods for flow applications - Teschner, Tom-Robin; Könözsy, László Z.; Jenkins, Karl W. (Springer, 2016)
This work focuses on the review of particle-based multiscale and hybrid methods that have surfaced in the field of fluid mechanics over the last 20 years. We consider five established particle methods: molecular dynamics, direct simulation Monte Carlo, lattice Boltzmann method, dissipative particle dynamics and smoothed-particle hydrodynamics. A general description is given on each particle method in conjunction with multiscale and hybrid applications. An analysis on the length scale separation revealed that current multiscale methods only bridge across scales which are of the order of O(102)−O(103) and that further work on complex geometries and parallel code optimisation is needed to increase the separation. Similarities between methods are highlighted and combinations discussed. Advantages, disadvantages and applications of each particle method have been tabulated as a reference.
Keywords: Multiscale simulations; Molecular dynamics; Direct simulation Monte Carlo; Lattice Boltzmann; Dissipative particle dynamics; Smoothed-particle hydrodynamics